Translation methods for translating cultural meanings of numerical conceptions in Chinese numerical proverbs - He, Zongjin; Wong, Ling Yann; Abdul Aziz, Adi Yasran (Human Resource Management Academic Research Society, 2024)
Language can be a reflection of a region, and history (Chen, 2009). Chinese numerical proverbs, considered as invaluable gems of China, are known for their concise yet profound nature. They encapsulate the essence of Chinese culture, which has a history spanning over 5000 years. Furthermore, the numerical concepts in these proverbs have strong connections to ancient Chinese philosophy, politics, and society. However, many native Chinese speakers tend to overlook the cultural and linguistic significance of numbers in Chinese proverbs. Instead, they opt to translate the proverbs using familiar and widely recognized English words, but in doing so, they neglect the cultural meanings indicated by the numerical concepts of the proverbs. This presents a challenge for non-native Chinese learners in comprehending the cultural meanings of numerical concepts in Chinese proverbs through English translation. Previous research has shown that some translators did not place much emphasis on investigating the cultural significance of numerical concepts, treating them as fictional with no textual reference. Therefore, based on research collected from CNKI (https://www.cnki.net/index), this study has gathered 132 studies on Chinese numerical proverbs, total with 46 journals, 2 books, 4 proceedings and 80 dissertations. Moreover, there are entirely 21 papers focus on exploring their cultural meanings. Qualitative research methods are being applied to gather and analyse research data. The analysis aims to uncovers the cultural meanings of Chinese numerical proverbs and their relationship with the ancient practices of Chinese society. The findings of this research will contribute to identifying relevant translation methods that can be used to convey the cultural meanings of Chinese numerical proverbs and address the issue of cultural loss in translations between Chinese and English.